Pencegahan Disabilitas pada Kusta - Thiodorus, Robert; Rusyati, Luh Made Mas; Sadeli, Marrietta Sugiarti (Fakultas Kedokteran Universitas Trisakti, 2023)
Leprosy, a chronic granulomatous infectious disease caused by Mycobacterium Leprae, presents a complex challenge with profound social, physical, and economic implications. The burden of leprosy is a persistent concern in many developing countries, despite substantial control efforts. The World Health Organization (WHO) initiated the